Estado cognitivo de los adultos mayores usuarios del dispensario del Seguro Social Campesino de la parroquia San Pedro de Vilcabamba - Merchán Mora, Ana Margarita (2020)
The existence of a close relationship between the decline in cognitive status as the aging process progresses has been of great interest and concern to health systems worldwide, as it implies a number of complications for older adults both in their daily lives and in family life. The rate of deterioration of cognitive functions involves multiple factors, so it becomes necessary to conduct research to understand the causes associated with greater or lesser cognitive impairment in old people. The general objective of the research was: to determine if there are significant differences in the cognitive status of elderly users of the Rural Social Security dispensary in San Pedro de Vilcabamba Parish. The research was carried out in the San Pedro de Vilcabamba parish, during the period 2020, on a population of 73 older adults, for which a sociodemographic record and Mini-Mental exam were applied. The main conclusion that was determined was that 34% of older adults had mild cognitive impairment, 18% moderate cognitive impairment and 4% severe dementia. The most affected cognitive areas were temporal orientation (37%), spatial orientation (48%), attention and calculation (32%); memory (44%), writing (41%) and drawing (38%). A significant correlation was also established with the age variable, since with increasing age in one year, the risk of cognitive deterioration in the elderly increases 2.41 times. KEY WORDS: cognition, cognitive dysfunction, dementia, aged